A survey of analysis on quantum algorithms for communication - Yuhong, Huang; Chunfeng, Cui; Chengkang, Pan; Shuai, Hou; Zhiwen, Sun; Xian, Lu; Xinying, Li; Yifei, Yuan (China communications, 2025)
Quantum computing is a promising technology that has the potential to revolutionize many areas of science and technology, including communication. In this review, we discuss the current state of quantum computing in communication and its potential applications in various areas such as network optimization, signal processing, and machine learning for communication. First, the basic principle of quantum computing, quantum physics systems, and quantum algorithms are analyzed. Then, based on the classification of quantum algorithms, several important basic quantum algorithms, quantum optimization algorithms, and quantum machine learning algorithms are discussed in detail. Finally, the basic ideas and feasibility of introducing quantum algorithms into communications are emphatically analyzed, which provides a reference to address computational bottlenecks in communication networks.